2019
DOI: 10.1371/journal.pone.0223782
|View full text |Cite
|
Sign up to set email alerts
|

Visual inputs decrease brain activity in frontal areas during silent lipreading

Abstract: AimThe aim of the present work is to analyze the modulation of the brain activity within the areas involved in lipreading when an additional visual stimulus is included.MethodsThe experiment consisted of two fMRI runs (lipreading_only and lipreading+picture) where two conditions were considered in each one (oral speech sentences condition [OSS] and oral speech syllables condition [OSSY]).ResultsDuring lipreading-only, higher activity in the left middle temporal gyrus (MTG) was identified for OSS than OSSY; dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…Visemes similarly modulated activity broadly through the STG, with increased BOLD at the posterior STG and decreased BOLD in the middle to anterior STG, along with increased BOLD in visual regions. The finding that lipreading suppresses neural activity within portions of the auditory system is consistent with prior reports from fMRI 24 and iEEG 25 , which has been theorized to reflect the optimized tuning of neurons specialized for auditory speech 26 .…”
Section: Resultssupporting
confidence: 89%
“…Visemes similarly modulated activity broadly through the STG, with increased BOLD at the posterior STG and decreased BOLD in the middle to anterior STG, along with increased BOLD in visual regions. The finding that lipreading suppresses neural activity within portions of the auditory system is consistent with prior reports from fMRI 24 and iEEG 25 , which has been theorized to reflect the optimized tuning of neurons specialized for auditory speech 26 .…”
Section: Resultssupporting
confidence: 89%
“…Furthermore, the SMA is crucial for sensorimotor integration involved in generating actions (Ruan et al, 2018 ). Notably, a recent fMRI study revealed that, during silent lipreading, brain activity in the SMA decreased when an additional visual stimulus was included (Plata Bello et al, 2019 ). Consistent with these findings, we observed that patients with TAO had decreased interhemispheric FC within the sensorimotor network, which suggests impaired sensorimotor function in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…The McGurk paradigm consists of the concurrent presentation of either congruent or incongruent auditory and visual signals [ 14 ]. Interpretations of Jenson et al [ 30 ] notwithstanding, the capacity for lip-reading [ 45 ] and visual speech identification [ 46 , 47 ] may be interpreted to suggest that the initial articulatory hypotheses supporting Analysis by Synthesis may be generated by either auditory or visual signals. It may then be proposed that in the McGurk paradigm, both visual and auditory streams give rise to independent articulatory hypotheses, which must be reconciled to allow the extraction of a unified phonological representation during working memory encoding.…”
Section: Introductionmentioning
confidence: 99%